2007
DOI: 10.1016/j.virol.2007.03.049
|View full text |Cite
|
Sign up to set email alerts
|

The cellular Mre11 protein interferes with adenovirus E4 mutant DNA replication

Abstract: Adenovirus type 5 (Ad5) relocalizes and degrades the host DNA repair protein Mre11, and efficiently initiates viral DNA replication. Mre11 associates with Ad E4 mutant DNA replication centers and is important for concatenating viral genomes. We have investigated the role of Mre11 in the E4 mutant DNA replication defect. RNAi-mediated knockdown of Mre11 dramatically rescues E4 mutant DNA replication in cells that do or do not concatenate viral genomes, suggesting that Mre11 inhibits DNA replication independent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
67
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(77 citation statements)
references
References 35 publications
9
67
1
Order By: Relevance
“…The proteins of the MRN complex recognize double-strand breaks in DNA to activate signaling pathways that result in repair by recombination or nonhomologous end joining (NHEJ) (14)(15)(16)(17). It is well established that when MRN components are not targeted for degradation by the virus-specific E3 Ub ligase or relocalized by the viral E4 Orf3 protein (8,18), viral DNA synthesis is impaired in infected cells (19)(20)(21). Furthermore, late in the infectious cycle, concatemers of randomly oriented copies of the viral genome are formed in NHEJ-dependent reactions (8,22,23).…”
mentioning
confidence: 99%
“…The proteins of the MRN complex recognize double-strand breaks in DNA to activate signaling pathways that result in repair by recombination or nonhomologous end joining (NHEJ) (14)(15)(16)(17). It is well established that when MRN components are not targeted for degradation by the virus-specific E3 Ub ligase or relocalized by the viral E4 Orf3 protein (8,18), viral DNA synthesis is impaired in infected cells (19)(20)(21). Furthermore, late in the infectious cycle, concatemers of randomly oriented copies of the viral genome are formed in NHEJ-dependent reactions (8,22,23).…”
mentioning
confidence: 99%
“…The Ad5 E4-ORF3 protein relocalizes nuclear proteins involved in a DDR, including Mre11, Rad50, and Nbs1 (the MRN complex) into the track structures (17,18). The available evidence suggests that E4-ORF3 inhibits the functions of these DNA repair proteins by a sequestration mechanism to block their access to the viral genome (17)(18)(19)(20)(21). The Ad5 E1B-55K⅐E4-ORF6 complex functions as an adaptor molecule in an E3 ubiquitin ligase complex (22,23).…”
mentioning
confidence: 99%
“…We have previously observed that the MRN sensor complex is needed for efficient Mdc1 focus formation in Ad-infected cells (31) and that both Mre11 and Mdc1 are bound to viral DNA at early times after infection in chromatin immunoprecipitation (ChIP) experiments (32). Mdc1 focus formation is correlated with MOI ( Fig.…”
Section: Discussionmentioning
confidence: 96%
“…We have previously found that Mdc1 focus formation can be observed by 4 hpi before the onset of viral DNA replication in both Ad5 and E4 mutant infections (31). AdRSV␤gal lacks E1 and is therefore deficient for both viral early gene expression and DNA replication (5).…”
Section: Mdc1 Focus Formation Is Correlated With the Moi And Requiresmentioning
confidence: 99%
See 1 more Smart Citation